New Highly Charged Iron(Iii) Metal-Organic Cube Stabilized by a Bulky Amine - Venegas-Yazigi, D; Venegas-Yazigi, D (American Chemical Society, 2020)
In this work, we report a new octanuclear cluster based on FeIII and the ligand 1H-imidazole-4,5-dicarboxylic acid, [Et3NH]12[Fe8(IDC)12]middot10DMF 13H2O (1), with a metal core containing eight FeIII connected by only one type of organic ligand. A peak at 573 m/z in the mass spectra of the compound suggests the adduct species {[Fe8(IDC)12]+8H}4-. By X-ray photoelectron spectroscopy, the oxidation state of the iron cation was confirmed to be 3+, also identifying the presence of a quaternary nitrogen species, which act as a countercation of the anionic metal core [Fe8(IDC)12]12-. Mössbauer spectra recorded at different temperatures show an isomer shift and quadrupole splitting parameters that confirm the existence of only FeIII-HS in the structure of 1. X-ray analysis reveals that compound 1 crystallizes in the orthorhombic system space group Ibam, confirming a molecular cluster structure with an almost regular cube as geometry, with the FeIII atoms located at the corners of the cube and connected by κ2N,O:2κ2N,Oâ IDC3- bridges. Additionally, the magnetic measurements reveal a weak antiferromagnetic coupling in the Fe8III coordination cluster (J =-3.8 cm-1). To the best of our knowledge, 1 is the first member of the family of cubes assembled with 1H-imidazole-4,5-dicarboxylic acid and FeIII cation, exhibiting high pH stability over a broad pH range, making it an ideal candidate for the design of supramolecular structures and metal-organic frameworks. Copyright © 2020 American Chemical Society.